MEMAHAMI PENDERITAAN DALAM 1 PETRUS 4:12-19 DAN IMPLIKASINYA DENGAN SITUASI PANDEMI COVID-19 - Enjelia Marthen; Dicky Dominggus (Bethel Press, 2021)
Abstract Suffering is something that is part of human life. This means that everyone must experience suffering. Suffering referred to can be in various kinds such as illness, economic hardship, discrimination, psychological pressure and others. Peter wrote suffering in the text of 1 Peter 4: 12-19. In this text, Peter is encouraging the congregation to endure the suffering they are experiencing. This research is a qualitative research with a grammatical historical approach. In this research, a study of the text of 1 Peter 4: 12-19 was conducted to find the original meaning of the suffering that Peter intended. Based on the research conducted, it can be concluded that the suffering referred to by Peter is suffering because of faith in Christ. As such, it is important for believers today to properly understand suffering as something that is normal for humans to face and is under God's sovereignty.